A satisfação do usuário em hospital universitário User satisfaction at a university hospital - Antonio C. Lemme; Gerson Noronha; José B. Resende (Universidade de São Paulo, 1991)
São apresentados resultados de uma pesquisa exploratória da satisfação/insatisfação de 158 pacientes que recorreram a um Hospital Universitário (HUPE) para consulta inicial. As entrevistas foram feitas por alunos do primeiro ano, como parte de projeto de inserção precoce do mesmo com a prática médica, acompanhando pacientes como observadores. Foi utilizado questionário que cobriu os vários aspectos do problema: variáveis sócio-demográficas, arte do cuidado, resolutividade da consulta médica, sugestões de melhoria dos serviços. Tanto alunos/observadores como os usuários conseguiram perceber com precisão os problemas do processo do atendimento (recepção, matrícula, consulta, enfermagem, serviço social, farmácia, exames complementares) mas houve divergência de opinião entre vários aspectos da satisfação/insatisfação entre alunos e usuários, provavelmente devido às origens sociais diferentes e expectativas diversas. The results of a research project into the level of satisfaction/dissatisfaction of 158 first-time patients attending by an University hospital, Brazil, are presented. The interviews were carried out by first year medical students as part of a comprehensive project concerned with the restructuring of the Medical Curriculum. Its prime objective was to expose the students to patients/consumers as early as possible in their studies. After an introductory training program, the students asked the patients arriving at the hospital out-patient clinic for permission to observe them throughout the attendance given. A questionnaire was used which covered the various aspects of the consumers relationship with a medical institution (socio-economic variables, "art of care", outcome of the medical encounter and suggestions for improvement). Both patients and students were able to perceive the different problems that patients confront in the course of their dealings with a medical institution (reception, registration, nursing, social service and medical attention). The data showed a difference of opinion between students and patients regarding several aspects of the satisfaction/dissatisfaction items, partly because of their different social class status and parthy due to the different expectations regarding medical care.